My Life Is A Mess: Self-Deprecating Relatability And The Memefication Of Student Publics - Ask, Kristine; Abidin, Crystal (AoIR Selected Papers of Internet Research, 2017)
Memes depicting student issues are growing in numbers and are gaining increased visibility in popular media outlets, making them a bona fide genre of memes. We consider these memes to be an expression of a new networked student public, and our analysis seek to bring forth student voices that might otherwise be silenced. Based on content analysis of posts on the submission based Facebook page “Student Problems”, this paper asks how higher education is framed by student memes, and what these memes may tell us about the lifeworld and collective identities of students. We also analyze the limitations of meme based publics, emphasising processes of inclusion and exclusion of minority identities through specific vernaculars of visual and discursive humour.